Let be the number of real solution(s) to the above equation and be the sum of all real solution(s). Find .
If you think it has no real solution enter 2018.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 + x 1 ) x + 1 ( x x + 1 ) x + 1 ⟹ x = ( 1 + 2 0 1 8 1 ) 2 0 1 8 = ( 2 0 1 8 2 0 1 9 ) 2 0 1 8 = ( 2 0 1 9 2 0 1 8 ) − 2 0 1 8 = ( − 2 0 1 9 − 2 0 1 9 + 1 ) − 2 0 1 9 + 1 = − 2 0 1 9
Therefore, α + β = 1 + ( − 2 0 1 9 ) = − 2 0 1 8 .